Food habits of the ocelot (leopardus pardalis) in a lowland atlantic forest of southeastern Brazil - Dos Santos, Joyce G. (2022)
The ocelot (Leopardus pardalis) has a diverse diet and contributes to the control of animal populations at intermediate trophic levels, acting as an e cient mesopredator. Here, we characterized the diet of L. pardalis in a remnant of lowland Atlantic Forest of southeastern Brazil, determining the species and the main prey items consumed (those with a percentage of occurrence [PO]≥5%), as well as its trophic specialization. We characterized L. pardalis diet using 30 fecal samples collected in the Vale Natural Reserve (Linhares/ES), between October 2014 and September 2016. Forty-nine food items were identi ed and distributed into 14 taxa, half of which were recognized as main prey (Cuniculus paca, Dasypus spp., Didelphis aurita, Mazama spp., Nasua nasua, Salvator merianae, and Sapajus robustus; 81.6% of the consumed items). Mammals were the most consumed (PO= 83.7%), followed by Reptilia (12.2%) and Aves (4.1%). Medium-sized prey (1-15 kg) were the most representative (PO= 84.9%), followed by large (>15 kg; 10.9%) and small prey (<1 kg; 4.3%). The diet was generalist when considering the consumption of individual prey (niche breadth= 0.641), but specialized in mammals (0.197) and medium-sized prey (0.181). High consumption of medium-sized mammals represents a foraging optimization strategy, as this prey type may be more energetically pro table for L. pardalis. The importance of some prey changed over time, suggesting temporal variation in the diet of this predator. We provided new information about the diet of the species, including the consumption of large prey (brocket deer of the genus Mazama). The local maintenance of a wide variety of prey may contribute to the conservation of this population over time.